Analysis of the profile of Brazilian fellowship researchers productivity in Physiotherapy: : observational study - Cardoso Silva, Michelly; Santana, Josimari Melo de (Revista Brasileira de Pós-Graduação, 2025)
In order to inform the scientific community about the profile of productivity researchers, several studies have been caried out. Considering the advancement of the Physical Therapy field in Brazil, it is necessary to examine the profile of productivity in this field. This is an observational, descriptive study. Initially, a list of all productivity researchers in the Physical Therapy area was obtained from National Council for Scientific and Technological Development. Free access was made to the information contained in the Lattes Curriculum. We identified 62 productivity researchers in Physical Therapy, with 75.8% located in the Southeast region and a slight predominance of women (54.8%). We note that 58% of the fellows are distributed in four universities. Regarding human resource training, researchers in the category 2 stand out for having the highest number of graduates. Among the specialties recognized by Brazilian Federal Council of Physical Therapy and Occupational Therapy, Trauma-Orthopedic, Respiratory and Neurofunctional PT stood out. Therefore, we observe that there is still heterogeneity in relation to the distribution of fellowships, with a predominance of female fellowship holders, with a great concentration in the Southeast region. We emphasize that the main research funding agencies highlighted by the researchers were Brazilian Federal Agency for Support and Evaluation of Graduate Education, National Council for Scientific and Technological Development and regional foundations.